2018
DOI: 10.29327/ouricuri.v8.i1.a3
|View full text |Cite
|
Sign up to set email alerts
|

Utilização Do Índice De Estado Trófico Para Análise Do Grau De Trofia Do Parque Aquícola Sucupira (Lago De Palmas, To) Na Estação Seca

Abstract: Aquaculture is the fastest growing activity among food production sectors, however, its practice can cause environmental impacts, in case if a monitoring plan is not applied. The objective of the present study was to evaluate the trophic environment status using the Trophic State Index (TSI) in an aquaculture activity in a netcage system in the Lajeado reservoir, Palmas, Tocantins during the dry season. The monitoring was carried out from May/2017 to August/2017 and involved the water sampling for analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…the risk of transmission of waterborne diseases may be lower(FUNASA, 2014).Similar studies, with sampling only during the dry season, have been carried out elsewhere(PEDROSO;COLESANTI, 2017;ROSANOVA et al, 2018;MUNIZ, 2019;POLHEIM;SCHEIN, 2019). Other research, carried out in the dry and rainy seasons, indicated superior quality in the dry season (SILVA; SÁ-OLIVEIRA, 2014; MEDEIROS; LIMA; GUIMARÃES, 2016; SILVA; CUNHA; LOPES, 2019).…”
mentioning
confidence: 84%
“…the risk of transmission of waterborne diseases may be lower(FUNASA, 2014).Similar studies, with sampling only during the dry season, have been carried out elsewhere(PEDROSO;COLESANTI, 2017;ROSANOVA et al, 2018;MUNIZ, 2019;POLHEIM;SCHEIN, 2019). Other research, carried out in the dry and rainy seasons, indicated superior quality in the dry season (SILVA; SÁ-OLIVEIRA, 2014; MEDEIROS; LIMA; GUIMARÃES, 2016; SILVA; CUNHA; LOPES, 2019).…”
mentioning
confidence: 84%